2015
DOI: 10.1007/s12274-015-0935-3
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for the treatment of CLL using chlorambucil/hydroxychloroquine-loaded anti-CD20 nanoparticles

Abstract: Current approaches for the treatment of chronic lymphocytic leukemia (CLL) have greatly improved the prognosis for survival, but some patients remain refractive to these therapeutic regimens. Hence, in addition to reducing the long-term sideeffects of therapeutics for all leukemia patients, there is an urgent need for novel therapeutic strategies for difficult-to-treat leukemia cases. Due to the cytotoxicity of drugs, the major challenge currently is to deliver the therapeutic agents to neoplastic cells while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The presence of specific proteins in tissue samples was confirmed by western blot performed as previously described [23]. Unfixed tissue samples from Patient 12 and control C were snap-frozen and embedded in OCT medium (Diagnostic Division; Miles Inc., Elkhart, IN, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The presence of specific proteins in tissue samples was confirmed by western blot performed as previously described [23]. Unfixed tissue samples from Patient 12 and control C were snap-frozen and embedded in OCT medium (Diagnostic Division; Miles Inc., Elkhart, IN, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…To overcome some of the limitations of standard anticancer drugs, they can be encapsulated inside biodegradable polymeric NPs which guarantees the delivery of the drug to the target site and a continuous and controlled release. Chlorambucil and hydroxychloroquine [ 110 112 ] or doxorubicin [ 113 ] are loaded inside biodegradable polymeric NPs and are functionalized with anti-CD20 or anti-CD19 antibodies to specifically target different neoplastic B-cells. Idarubicin, an anthracycline antibiotic approved by FDA analogue to daunorubicin, can be encapsulated in methoxy poly(ethylene glycol)-b-poly(l-lactide-co-glycolide) nanoparticles [ 114 ].…”
Section: Nanoparticle-based Therapymentioning
confidence: 99%
“…It is important to point out that tumor cells are often heterogeneous in the expression level of tumor antigens that may influence their susceptibility to CDC. We have observed that cells expressing low levels of CD20 isolated by cell sorting from a population of either chronic lymphocytic leukemia (CLL) or cancer B-cell lines and kept in culture for over a week give rise to cells expressing higher level of CD20 that more easily undergo C-mediated lysis ( 40 , 41 ). This observation suggests that repeated injections of Abs administered at appropriate time intervals can be used to allow the emergence of cell clones expressing higher levels of CD20 and more susceptible to CDC.…”
Section: Factors Affecting the Efficiency Of The Antibodies To Activamentioning
confidence: 99%